Educator and Student Interaction in Creating Positive Relationships in the Classroom - Ode Yahyu Herliany Yusuf; Nurani Nurani; Nurwia Sandy; Lisnawati Sarpan; Emiyati Emiyati; Ayu Selfia (CV. Rayyan Dwi Bharata, 2023)
The purpose of this study is to determine the interaction of educators and students in creating positive relationships in the classroom. Where educators must have the ability to build positive interaction relationships with children. So as to create a comfortable and safe atmosphere for children. This research uses a type of qualitative research in the form of a literature study (Library Research) Literature studies are related to theoretical studies based on data in the form of notes, books, papers or articles, journals and other scientific literature references. The results showed that an educator must be able to create a sense of security and comfort for children, especially for children from chaotic families. Because a positive relationship with teachers and children can foster confidence in children towards teachers.